Effects of humidity and interlayer cations on the frictional strength of montmorillonite - Hiroshi Tetsuka; Ikuo Katayama; Hiroshi Sakuma; Kenji Tamura (Earth, Planets and Space, 2018)
Abstract We developed a humidity control system in a biaxial friction testing machine to investigate the effect of relative humidity and interlayer cations on the frictional strength of montmorillonite. We carried out the frictional experiments on Na- and Ca-montmorillonite under controlled relative humidities (ca. 10, 30, 50, 70, and 90%) and at a constant temperature (95 °C). Our experimental results show that frictional strengths of both Na- and Ca-montmorillonite decrease systematically with increasing relative humidity. The friction coefficients of Na-montmorillonite decrease from 0.33 (at relative humidity of 10%) to 0.06 (at relative humidity of 93%) and those of Ca-montmorillonite decrease from 0.22 (at relative humidity of 11%) to 0.04 (at relative humidity of 91%). Our results also show that the frictional strength of Na-montmorillonite is higher than that of Ca-montmorillonite at a given relative humidity. These results reveal that the frictional strength of montmorillonite is sensitive to hydration state and interlayer cation species, suggesting that the strength of faults containing these clay minerals depends on the physical and chemical environment.